Optimalisasi Biaya Pendistribusian Keramik Menggunakan Least Cost Method dengan Uji Optimal Modified Distribution Method (Modi) (Studi Kasus: PT. Indah Bangunan Sejati Palu) - Syahdi; Resnawati; Andri (Program Studi Matematika, Universitas Tadulako, 2023)
PT. Indah Bangunan Sejati Palu is a company engaged in building materials. The company has 4 warehouses and serves the distribution of ceramics in Sulawesi Tengah, precisely in the city of Palu. The problems found in PT. Indah Bangunan Sejati Palu The cost of distributing ceramics requires a large amount of transportation costs and there is no planning for the distribution of ceramics, therefore proper planning is needed so that the distribution costs incurred can be minimized. The purpose of this study is to obtain optimal distribution costs using the least cost method with the optimal test using the Modified Distribution (MODI) method. The results showed that the optimal transportation cost was obtained at Rp 276,297,300. This amount is more efficient, namely Rp 3,002,400 or 1.1% of the company's transportation costs which is Rp 279,297,300.